2015
DOI: 10.1186/s12978-015-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of a fertility experiences questionnaire

Abstract: BackgroundMany women throughout the world have history of subfertility (resolved or unresolved), but much remains unknown about services and treatments chosen.MethodsWe developed a mixed-mode fertility experiences questionnaire (FEQ) in 2009 through literature review and iterative pilot work to optimize question format and mode of administration. The focus of the FEQ is to collect data retrospectively on time at risk for pregnancy, fertility treatments received and declined, pregnancy, time to pregnancy and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The validity of self-reported fertility diagnosis is less certain, but at least some types of diagnoses have been found to be reported accurately in questionnaires by educated women (38,39). We sought to minimize problems with recall for treatment by the multimode, two stage questionnaire (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of self-reported fertility diagnosis is less certain, but at least some types of diagnoses have been found to be reported accurately in questionnaires by educated women (38,39). We sought to minimize problems with recall for treatment by the multimode, two stage questionnaire (24).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to medical records, the FEQ was over 90% sensitive for pregnancy attempt duration, pregnancy outcomes, and use of IVF and IUI, and 70% sensitive for the use of ovulation drugs. (24) Data from 2000 to 2010 Utah birth and fetal death certi cates were linked with data from women who completed both the online questionnaire and the structured telephone interview. The University of Utah Institutional Review Board approved this study; participants provided informed consent online prior to completing the initial questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous validation study found high levels of correlation between patient self-report and medical records for time attempting to conceive (Pearson’s rho=0.61), pregnancy and live birth histories (kappa=0.70), and use of in vitro fertilization (kappa=0.77). 15 For each period of time during which a woman was attempting to conceive, interviewers asked, “During this period did you see a doctor or provider specifically for fertility-related issues?” If yes, she was then asked, “Did you meet or consult with: A general physician/provider (obstetrician, family medicine physician, physician assistant, nurse midwife, nurse practitioner)?A fertility specialist?Utah Center for Reproductive Medicine (UCRM)?Reproductive Care Center (RCC)?Out of state?An alternative/holistic practitioner (chiropractor, acupuncturist, naturopath, etc. )?…”
Section: Methodsmentioning
confidence: 99%
“…During this interview, more detailed questions reassessed screening criteria, but women's eligibility was not altered by any responses at this stage. We have reported elsewhere an initial validation of several components of the FEQ, the sources used to develop it, and its contents …”
Section: Methodsmentioning
confidence: 99%